2023
DOI: 10.1101/2023.06.29.547047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of novel DNA cytosine deaminase activities enables a nondestructive single-enzyme methylation sequencing method for base resolution high-coverage methylome mapping of cell-free and ultra-low input DNA

Romualdas Vaisvila,
Sean R. Johnson,
Bo Yan
et al.

Abstract: Cytosine deaminases have important uses in the detection of epigenetic modifications and in genome editing. However, the range of applications of deaminases is limited by a small number of well characterized enzymes. To expand the toolkit of deaminases, we developed an in-vitro approach that bypasses a major hurdle with their severe toxicity in expression hosts. We systematically assayed the activity of 175 putative cytosine deaminases on an unprecedented variety of substrates with epigenetically relevant base… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Recent biochemical studies conducted in vitro have shown that the enzyme SsdAtox possesses cytosine deamination activity on ssDNA. Interestingly, at elevated concentrations, SsdAtox also exhibits the ability to deaminate cytosine in dsDNA (14,33). To further explore the potential of SRE variant in mediating cytosine deamination within dsDNA genomes, we engineered fusions of SRE variant with TALE constructs, named TALE-SRE, akin to DdCBE systems, which is incorporating UGI and a nuclear localization signal (NLS) (5).…”
Section: The Versatility Of Sscbe1-srementioning
confidence: 99%
“…Recent biochemical studies conducted in vitro have shown that the enzyme SsdAtox possesses cytosine deamination activity on ssDNA. Interestingly, at elevated concentrations, SsdAtox also exhibits the ability to deaminate cytosine in dsDNA (14,33). To further explore the potential of SRE variant in mediating cytosine deamination within dsDNA genomes, we engineered fusions of SRE variant with TALE constructs, named TALE-SRE, akin to DdCBE systems, which is incorporating UGI and a nuclear localization signal (NLS) (5).…”
Section: The Versatility Of Sscbe1-srementioning
confidence: 99%